A Topographical Approach to Re-Reading Books about Islands in Digital Literary Spaces - Carpenter, J. R. (MATLIT: Materialities of Literature, 2016)
This article takes a topographical approach to re-reading print books in digital literary spaces through a discussion of a web-based work of digital literature, …and by islands I mean paragraphs (Carpenter 2013). In this work, a reader is cast adrift in a sea of white space extending far beyond the bounds of the browser window, to the north, south, east and west. This sea is dotted with computer-generated paragraphs. These fluid texts call upon variable strings containing words and phrases collected from a vast literary corpus of books about islands. Individually, each of these textual islands represents a topic—from the Greek topos, meaning place. Collectively they constitute a topographical map of a sustained practice of reading and re-reading and writing and re-writing on the topic of islands. This article argues that, called as statement-events into digital processes, fragments of print texts are reconstituted as events occurring in a digital present which is also a break from the present. A new regime of signification emerges, in which authorship is distributed and text is ‘eventilized’ (Hayles). This regime is situated at the interface between an incoherent aesthetics, one which tends to unravel neat masses, including well-known works of print literature; and an incoherent politics, one which tends to dissolve existing institutional bonds, including bonds of authorship and of place. Galloway terms this regime of signification the ‘dirty regime of truth’. DOI: http://dx.doi.org/10.14195/2182-8830_4-1_5